2012
DOI: 10.1086/bblv222n1p35
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Patterns of Diurnal Activity in the Box Jellyfish Tripedalia cystophora and Copula sivickisi

Abstract: Cubozoan medusae have a stereotypic set of 24 eyes, some of which are structurally similar to vertebrate and cephalopod eyes. Across the approximately 25 described species, this set of eyes varies surprisingly little, suggesting that they are involved in an equally stereotypic set of visual tasks. During the day Tripedalia cystophora is found at the edge of mangrove lagoons where it accumulates close to the surface in sun-lit patches between the prop roots. Copula sivickisi (formerly named Carybdea sivickisi) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 28 publications
0
39
0
1
Order By: Relevance
“…Although future studies are required to test whether other cnidarians sleep, field studies showing behavioral quiescence, diel vertical migration, and swimming speeds that vary with diel period [21,22,23,37] suggest that a sleep-like state may not be specific to Cassiopea . A cnidarian sleep-like state could result from either divergent or convergent evolution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although future studies are required to test whether other cnidarians sleep, field studies showing behavioral quiescence, diel vertical migration, and swimming speeds that vary with diel period [21,22,23,37] suggest that a sleep-like state may not be specific to Cassiopea . A cnidarian sleep-like state could result from either divergent or convergent evolution.…”
Section: Resultsmentioning
confidence: 99%
“…In Cnidaria, neurons are organized into a non-centralized radially symmetric nerve net [11,13,1517] that nevertheless shares fundamental properties with the vertebrate nervous system: action potentials, synaptic transmission, neuropeptides, and neurotransmitters [1520]. It was reported that cnidarian soft corals [21] and box jellyfish [22,23] exhibit periods of quiescence, a pre-requisite for sleep-like states, prompting us to ask if sleep is present in Cnidaria. Within Cnidaria, the upside-down jellyfish Cassiopea spp.…”
mentioning
confidence: 99%
“…The other, larger lens eye is oriented downwards. The eyes allow the medusae to navigate effi ciently through their mangrove habitat, to avoid predators and actively pursue prey (Garm et al 2007a(Garm et al , b , 2008(Garm et al , 2012Petie et al 2011 ).…”
Section: Aurelia Aurita and Tripedalia Spmentioning
confidence: 99%
“…de). But besides this, the group also presents other interesting aspects, like courtship (Lewis & Long 2005, Lewis et al 2008, Garm et al 2012, Chiaverano et al 2013, Canepa et al 2014, Carrette et al 2014, vision (Coates 2003, Nordström et al 2003, Nilsson et al 2005, Garm et al 2006, 2007a+b, 2008, Garm & Bielecki 2008 and taxonomic classification (Bigelow 1938, Werner 1973, Gershwin 2005b, 2006, Straehler-Pohl 2014, Toshino et al 2013. Also the validity of some species, especially the ones of the alatinid family, has been discussed since the beginning of the last century (Mayer 1910, Bigelow 1938, Kramp 1961, Gershwin 2005a, b, Bentlage 2010, Lewis et al 2013.…”
Section: Introductionmentioning
confidence: 99%